The Use of Powerpoint Media to Increase Student Learning Motivation at MTs Mamba'ul Ulum Margoyoso Lampung - Muslihatun; Mu'tashom (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning using powerpoint media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of junior high school. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that powerpoint media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 49.71%, the first cycle 69.39% and in the second cycle it increased to 89.66%. Thus, the use of powerpoint media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.